Psychological Well-Being for Women Working as Members of the TNI/Polri - R.R. Karina Putri Pramitadewi; Wiwin Hendriani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The purpose of this study is to collaborate the results of previous research on psychological well-being in women who work as members of the TNI/Polri into a study. This study uses literature studies. The usefulness of literature review itself is to synthesize a variety of relevant research results, so that the facts presented can be more balanced and comprehensive. A total of four journals will be reviewed after going through the selection process, all of which are journals with quantitative studies. The results of the study described on the condition of psychological well-being in women who worked as members of the TNI/Polri based on the results of measurements in the journal 1 showed that most (71%) were in the high category. While the results of measurements in journal 4 showed 62.5% of psychological well-being was in the high category and 37.5% very high. Based on the results of this study, it can be used as reinforcing evidence for the importance of paying more attention, especially to the psychological well-being of women who work as members of the TNI/Polri, which have a positive or negative relationship with several other variables such as Dual Role Conflict (Work-Family), Hardiness, Perceptions of Career Development and Fear of Success.Penelitian ini bertujuan untuk mengkolaborasikan hasil penelitian sebelum-sebelumnya perihal kesejahteraan psikologi pada wanita yang bekerja sebagai anggota TNI/Polri menjadi sebuah kajian. Penelitian ini menggunakan kajian literatur. Kegunaan dari tinjauan literatur sendiri adalah untuk mensintesis berbagai hasil penelitian yang relevan, sehingga fakta yang dipaparkan dapat lebih berimbang dan juga komprehensif. Sebanyak empat jurnal akan ditinjau setelah melalui proses seleksi, yang semuanya merupakan jurnal dengan studi kuantitatif. Hasil penelitian yang digambarkan perihal kondisi kesejahteraan psikologis pada wanita yang bekerja sebagai anggota TNI/Polri berdasarkan dari hasil pengukuran dalam jurnal 1 menunjukkan bahwa sebagian besar (71%) berada pada kategori tinggi. Sedangkan hasil pengukuran pada jurnal 4 menunjukkan 62,5% kesejahteraan psikologis berada pada kategori tinggi dan 37,5% sangat tinggi. Hasil penelitian ini dapat dijadikan sebagai bukti penguat pentingnya untuk memberikan perhatian lebih khususnya terhadap kondisi kesejahteraan psikologis pada wanita yang bekerja sebagai anggota TNI/Polri yang memiliki hubungan baik secara positif maupun negatif dengan beberapa variabel lain seperti Konflik Peran Ganda (Pekerjaan-Keluarga), Hardiness, Persepsi Pengembangan Karier dan Fear of Success.